China's aerospace strategy - Singh, J. V. (Jitendra Vikram) (KW Publishers in association with Centre for Air Power Studies, 2013)
China has emerged as a major regional power and has clear aspirations to be a global power in the not too distant future. Comprehensive military modernisation programs, sustained economic, scientific and technological developments have substantially elevated China's international profile. For the past three decades, China has been modernising its strategic weaponry and enhancing the capabilities of its nuclear warheads. It has also been developing new and complex military platforms that would be of great value to joint operations warfare